Person-environment fit of formal and informal caregivers for older adults: a scoping review - Yuting Huang; Vivian Weiqun Lou; Wenling Zhang; Gehao Yang; Xiaobo Ke; Fan Yang; Haochu Li; Junyao Zheng; Yiyan Zhou; Wenjie Li; Shihan Lu (BMC Nursing)
Abstract Background Caring for older adults is a dynamic and complex process, and analyzing personal and environmental factors separately fails to capture its full nature. The person-environment fit theory offers a valuable framework to explore interactions between caregivers and their environments. This review aimed to synthesize evidence on the person-environment fit of formal and informal caregivers for older adults, identify gaps in existing literature, and propose future research directions. Methods The scoping review was conducted following the six-step guidance of the Joanna Briggs Institute 2020. A literature search was conducted in June 2024 across seven databases: Scopus, ProQuest, Web of Science, Embase, PubMed, MEDLINE, and CINAHL. Empirical studies published after 2000 regarding the person-environment fit of caregivers for older adults were included. Results A total of 15 eligible articles were included, with nine focusing on formal caregivers and six focusing on informal caregivers. Research on formal caregivers’ person-environment fit often came from human resource management perspectives and was supported by various theories. In contrast, studies on informal caregivers tended to draw from environmental gerontology theories and lacked a systematic analytical model. Most studies used self-designed questionnaires or interviews, with one employing a standard person-environment fit measurement scale. Caregivers’ person-environment fit was analyzed through “demands-abilities fit” and “needs-supplies fit” dimensions, covering various types like person-physical, person-interpersonal, value, goal, and caregiving-life fit. Findings indicated that a high level of person-environment fit was associated with better physical and mental well-being, stronger caregiving commitment, and improved care quality. Conclusion The holistic and dynamic nature of person-environment fit theory is closely aligned with the caregiving process, enhancing our understanding of the experiences of caregivers. Based on existing evidence, this review proposes a theoretical framework for analyzing informal caregivers’ person-environment fit. Further investigation into the theoretical framework of caregiver person-environment fit, along with the development of standardized assessment instruments, will significantly advance the well-being of both caregivers and care recipients. Trial registration Open Science Framework https://doi.org/10.17605/OSF.IO/YV26C .